Evidence‐based surgical guidelines for treating children with Wilms tumor in low‐resource settings. Issue 12 (5th August 2022) - Abdelhafeez, Abdelhafeez H.; Reljic, Tea; Kumar, Ambuj; Banu, Tahmina; Cox, Sharon; Davidoff, Andrew M.; Elgendy, Ahmed; Ghandour, Khalil; Gerstle, J. Ted; Karpelowsky, Jonathan; Kaste, Sue C.; Kechiche, Nahla; et al.
Abstract: Background: Survival of Wilms tumor (WT) is > 90% in high‐resource settings but < 30% in low‐resource settings. Adapting a standardized surgical approach to WT is challenging in low‐resource settings, but a local control strategy is crucial to improving outcomes. Objective: Provide resource‐sensitive recommendations for the surgical management of WT. Methods: We performed a systematic review of PubMed and EMBASE through July 7, 2020, and used the GRADE approach to assess evidence and recommendations. Recommendations: Initiation of treatment should be expedited, and surgery should be done in a high‐volume setting. Cross‐sectional imaging should be done to optimize preoperative planning. For patients with typical clinical features of WT, biopsy should not be done before chemotherapy, and neoadjuvant chemotherapy should precede surgical resection. Also, resection should include a large transperitoneal laparotomy, adequate lymph node sampling, and documentation of staging findings. For WT with tumor thrombus in the inferior vena cava, neoadjuvant chemotherapy should be given before en bloc resection of the tumor and thrombus and evaluation for viable tumor thrombus. For those with bilateral WT, neoadjuvant chemotherapy should be given for 6–12 weeks. Neither routine use of complex hilar control techniques during nephron‐sparing surgery nor nephron‐sparing resection for unilateral WT with a normal contralateral kidney is recommended. When indicated, postoperative radiotherapy should be administered within 14 days of surgery. Post‐chemotherapy pulmonary oligometastasis should be resected when feasible, if local protocols allow omission of whole‐lung irradiation in patients with nonanaplastic histology stage IV WT with pulmonary metastasis without evidence of extrapulmonary metastasis. Conclusion: We provide evidence‐based recommendations for the surgical management of WT, considering the benefits/risks associated with limited‐resource settings.